1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Finding a point on a surface which is closest to given point

  1. Nov 6, 2015 #1
    1. The problem statement, all variables and given/known data
    Find the point on the surface z2 = xy + y + 3 which is closest to the point (1,2,0)

    2. Relevant equations

    3. The attempt at a solution
    Can someone check my work?
  2. jcsd
  3. Nov 6, 2015 #2


    User Avatar
    Science Advisor

    I used a slightly different method, "Lagrange Multipliers", and got the same answer so it looks good!
  4. Nov 6, 2015 #3
    curious to see which way is method, I haven't learned that yet.
    Last edited: Nov 6, 2015
  5. Nov 6, 2015 #4


    User Avatar
    Science Advisor

    The "Lagrange Mulltipliers" method uses the fact that the shortest distance from a point to a surface is always perpendicular to the surface. So a vector in the direction of the line of shortest distance is parallel to a vector perpendicular to the surface. Given the function D(x, y, z)= (x- 1)^2+ (y- 2)^2+ z^2, The vector -(Dx i+ Dyj+ Dzk)= -(2(x- 1)i+ 2(y- 2)j+ 2zk) points along the line of fastest decrease of distance. We can write the surface as G(x, y, z)= xy+ y+ 3- z^2= 0 which has gradient vector nabla G= yi+ (x+ 1)j- 2zk perpendicular to the surface. So those two vectors must be parallel which means one is a multiple of the other: -(2(x- 1)+ 2(y- 2)+ 2z= lambda (yi+ (x+ 1)j- 2zk) where lambda is the "Lagrange Multiplier".

    Setting the same component equal we have the three equations, -2x+ 2= lambda y, -2y+ 4= lambda (x+ 1), and -2z= -2 lambda z. That is three equations in four unknowns, but we also have the equation of the surface, z^2= xy+ y+ 3. From -2z= -2 lambda z, we must have either z= 0 or lambda= 1. The first two equations, with lambda= 1, become -2x+ 2= y and -2y+ 4= x+ 1. With y= -2x+ 2, -2y+ 4= -2(-2x+ 2)+ 4= 4x- 4+ 4= 4x= x+ 1 so 3x= 1, x= 1/3. Then y= -2x+ 2= -2(1/3)+3= -2/3+ 6/3= 4/3. From that z^2= (1/3)(4/3)+ 4/3+ 3= 4/9+ 12/9+ 27/9= 43/9. So z= +/- sqrt(43)/3.

    (One can show that z= 0, which is the same as saying xy+ y+ 3= 0, cannot give a minimum distance.)
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook

Have something to add?
Draft saved Draft deleted